Statistical analysis of study results - Janilionis, Vytautas (Lietuvos matematikos rinkinys, 1997)
The methodics for statistical analysis of study results data bases and calculation of ratings of secondary schools marks are presented. Methodics are created using methods of applied statistics and realized in programs. Using them the statistical analysis of 1990-95 years Kaunas University of technology data bases is carried out, ratings of secondary schools marks are calculated. These ratings are being used for the admission to the University.